Propuesta de creación de un área protegida para la conservación del patrimonio natural del cantón Bolívar - Cedeño Ganchozo, Oscar Eduardo (2025)
The present study proposed the creation of a protected area in the Tordo site micro-watershed, Bolívar canton, with the aim of ensuring the conservation of natural heritage, biodiversity, and water resources. A territorial diagnosis was conducted, including inventories of flora and fauna, identification of water sources, and assessment of local productive activities, applying a participatory approach with nine experts from the Ministry of Environment specialized in environmental management, tourism, and community development, whose knowledge was evaluated to validate the strategies. A strategic analysis was carried out using the SWOT matrix, and a comprehensive action plan was developed. The results show that the Tordo site possesses high diversity, with 64 flora species, 15 mammal species, 10 bird species, 6 fish species, 87.10 hectares of primary forest, and a large micro-watershed as a vital resource, thus consolidating its ecological value with a Protected Forest. The validation of strategies is based on four main pillars: conservation of natural resources, community development, environmental and tourism education and awareness, and monitoring and evaluation. In conclusion, the implementation of this participatory and sustainable management model allows for the protection of biodiversity, ensures the conservation of water resources, maintains ecological connectivity, and promotes active community participation, constituting a replicable reference for the planning and management of micro-watersheds with similar characteristics.